Strategies for Transition to Sustainable Business Models (SBMs) in Key Manufacturing Sectors in India - Agarwal, Nitin (Digital Repository of Theses - SSBM Geneva, 2025)
The transition to Sustainable Business Models (SBMs) in the Indian manufacturing sector is hindered by financial constraints, resource limitations, managerial resistance, and sector-specific adoption barriers. While sustainability awareness has increased, implementation remains fragmented, with significant gaps between intent and execution. This study investigates the challenges, awareness levels, strategic approaches, stakeholder collaboration, and innovation drivers influencing SBM adoption across key manufacturing industries in India. A quantitative research methodology was employed, with primary data collected from 153 respondents across major manufacturing sectors, including Chemicals & Plastics, Infrastructure, Steel & Cement, Automobile & Transportation, Consumer Electronics & Capital Goods, Pharmacy & Healthcare, Textiles, and Agriculture & Food Processing. Statistical techniques such as ANOVA, Chi-Square, Kruskal-Wallis H Test, T-Test, and Multiple Regression Analysis were applied to assess sectoral differences, identify key challenges, and explore the factors affecting sustainability-driven innovation. The findings reveal that resource unavailability, high developmental costs, and managerial hesitancy are the most significant obstacles to SBM adoption. Chemicals & Plastics, Infrastructure, Steel & Cement, and Pharmacy & Healthcare sectors face the greatest challenges, particularly regarding financial constraints, operational inefficiencies, and lack of industry-wide collaboration. While awareness of sustainability practices is growing, many industries remain in early or mid-level stages of preparedness, with structured implementation still limited. Companies in the Automobile & Transportation and Consumer Electronics & Capital Goods sectors demonstrate relatively higher engagement, while Textiles and Agriculture & Food Processing lag in structured sustainability transitions. Circular economy principles, digital transformation, and green supply chain initiatives are emerging as key drivers of sustainability adoption. However, industry collaboration remains low, with many firms reluctant to share knowledge or engage in joint sustainability efforts with competitors. Financial incentives, policy interventions, andstronger managerial commitment are identified as essential enablers for accelerating the transition toward sustainable practices. This study contributes to the discourse on sustainable manufacturing in India by offering sector-specific insights, strategic recommendations, and policy implications. Addressing the identified barriers through financial support mechanisms, regulatory reforms, and cross-industry collaboration will be crucial in fostering a more sustainable and competitive manufacturing landscape in India.